2001
DOI: 10.1046/j.1462-5822.2001.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mycobacterium tuberculosis protein associated with mammalian cell entry

Abstract: The ability to gain entry and resist the antimicrobial intracellular environment of mammalian cells is an essential virulence property of Mycobacterium tuberculosis. A purified recombinant protein expressed by a 1362 bp locus (mce1) in the M. tuberculosis genome promoted uptake into HeLa cells of polystyrene latex microspheres coated with the protein. N‐terminus deletion constructs of Mce1 identified a domain located between amino acid positions 106 and 163 that was needed for this cell uptake activity. Mce1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
150
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(160 citation statements)
references
References 19 publications
10
150
0
Order By: Relevance
“…Mammalian cell entry (Mce) proteins were initially characterized as invasion-like proteins with putative export signal sequences at the N-terminal end (16,17). Previous studies suggest that latex beads coated with Mce1A, Mce3A, and Mce3E are internalized by nonphagocytic HeLa cells (18,19). Additional studies have demonstrated that the M. tuberculosis strains with mce operon disruption were attenuated in mice (20,21).…”
mentioning
confidence: 99%
“…Mammalian cell entry (Mce) proteins were initially characterized as invasion-like proteins with putative export signal sequences at the N-terminal end (16,17). Previous studies suggest that latex beads coated with Mce1A, Mce3A, and Mce3E are internalized by nonphagocytic HeLa cells (18,19). Additional studies have demonstrated that the M. tuberculosis strains with mce operon disruption were attenuated in mice (20,21).…”
mentioning
confidence: 99%
“…Originally thought to be simply involved in gaining entry to host cells, 3 more recent work 9 suggests that the Mce1 protein complex is also involved in the recycling of extracellular mycolic acids for use as a carbon source. Of particular interest, we show that the genes that were significantly upregulated by the macrophages in the period immediately after infection by M. tuberculosis H37Rv, but not D-mce1 H37Rv, were primarily involved in substrate trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…13 Besides being used as an energy source, cholesterol is essential for receptormediated internalization through clathrin-coated pits. 14 Previous studies have suggested that the active domain of the Mce1 protein complex for gaining entry into the host cell is a 58 amino acid long domain located between position 105 and 163 of the Mce1; the most hydrophilic part of the protein, 3,15 and that this peptide induces a membrane invagintion with structures resembling clathrin-coated pits. 3 For this study, the upregulation of the gene Abca1 by 15 min was only observed post H37Rv infection (18.5-fold) and not post D-mce1 H37Rv (1.8-fold), suggesting that the Mce1 protein complex is involved in the manipulation of cholesterol efflux during the initial stages of infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations